Transient Analysis of a Queueing System Incorporating the Effects of Feedback, Randomly Changing States and Catastrophes - Darvinder Kumar (International Journal of Intelligent Systems and Applications in Engineering, 2024)
In this paper, a limited capacity queueing system incorporating the effects of feedback, randomly changing states and catastrophes is studied. The effect of two randomly changing states are taken to be a function of the number of customers present in the system. We undertake the transient analysis of a limited capacity queueing system with two randomly changing states in the presence of feedback and catastrophes. Transient solution of the queueing model is obtained by using the probability generating function technique. Some interesting particular cases of the queueing model with (without) feedback and catastrophes are obtained. Measures of effectiveness and steady state solutions of the model are also discussed.